[Homes by Lava at Eldfell] - Streng, Evelyn Fiedler (1975)
Photograph of homes along lava rock at Eldfell. Brown, rounded mountains tower over the buildings in the background under wispy, white clouds. Two, rectangular, distressed buildings with red roofs sit in the foreground, the windows and doors covered in cardboard and blue metal plates. A black hill sits along the houses to the left covered in loose rubble.